-2a plus 3b
4a + 3c - 2b - c + a - b = 5a - 3b + 2c
It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus
Gathering like terms together, this is equal to 5a + 3b + 7c.
5a(2b + 1)
(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].
The given expression can be simplified to: 3b-a
This is not a difficult factorisation, as it is merely a normal factorisation with "a" stuck on the end of each number. 25a(2) - 20ab + 4b(2) (2b-5a)(2b-5a) This is: 2bx2b=4b(2) 2bx-5a=-10ab (twice) -5ax-5a=25a
It is not an equation but an algebraic expression that can be simplified to: 12b-5a
12a + 6b + 6c = 6(2a + b + c)
6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b
2a + 3b
6a+7b. This cannot be simplified anymore unless you know a or b.